2015
DOI: 10.1038/ncomms8577
|View full text |Cite
|
Sign up to set email alerts
|

Stereomicroscopic 3D-pattern profiling of murine and human intestinal inflammation reveals unique structural phenotypes

Abstract: Histology is fundamental to assess two-dimensional intestinal inflammation; however, inflammatory bowel diseases (IBDs) are often indistinguishable microscopically on the basis of mucosal biopsies. Here, we use stereomicroscopy (SM) to rapidly profile the entire intestinal topography and assess inflammation. We examine the mucosal surface of >700 mice (encompassing >16 strains and various IBD-models), create a profiling catalogue of 3D-stereomicroscopic abnormalities and demonstrate that mice with comparable h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 69 publications
0
111
0
Order By: Relevance
“…A complex microbial community was insufficient for generating a robust population of Th17 cells in the gut of SPF mice lacking SFB (9, 10) and gnotobiotic mice colonized long term with human fecal contents (42). Although SFB has been detected in multiple vertebrate species (43), there exists only sparse evidence of a related microbe colonizing humans (43)(44)(45)(46). A recent study showed that a consortium of 20 symbionts from the feces of an IBD patient could induce Th17 cells in mice but failed to identify the active microbes in healthy people (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complex microbial community was insufficient for generating a robust population of Th17 cells in the gut of SPF mice lacking SFB (9, 10) and gnotobiotic mice colonized long term with human fecal contents (42). Although SFB has been detected in multiple vertebrate species (43), there exists only sparse evidence of a related microbe colonizing humans (43)(44)(45)(46). A recent study showed that a consortium of 20 symbionts from the feces of an IBD patient could induce Th17 cells in mice but failed to identify the active microbes in healthy people (11).…”
Section: Discussionmentioning
confidence: 99%
“…These pathways could potentially regulate the activity of mechanosensitive integrins and cytokines (e.g., TGF-β) relevant to Th17 cell differentiation and trafficking. Interestingly, DNA from SFB-like microbes was recently enriched in the gut of human IBD patients, associated with cavernous fistulous tracts running between muscle bundles (46). The enrichment for muscle-related pathways in whole-tissue SI-LP preparations from mice colonized with B. adolescentis hints at a more general relationship between Th17-inducing microbes and intestinal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional stereomicroscopy assessment and pattern profiling serve to map and quantify the intestinal health in mice and to determine the extent of mucosal involvement that occurs with acute and chronic inflammation (18). To analyze the variable patterns of stereomicroscopic abnormalities, stereomicroscopy photographs were analyzed using ImageJ public domain software (imagej.nih.gov/ij/).…”
Section: Methodsmentioning
confidence: 99%
“… 19 Early alterations in epithelial architecture and defective barrier function are present by 3 weeks of age, preceding the onset of overt ileitis, and include increased numbers of secretory Paneth, goblet, and intermediate cells, with a simultaneous reduction in absorptive enterocytes. This trend increases at sites of active inflammation as the animals age and as the disease becomes more severe 20, 21.…”
Section: Mouse Models Of Cd-like Ileitismentioning
confidence: 99%